2002
DOI: 10.1016/s0025-5564(02)00119-0
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence relationships between stage-structured population models

Abstract: Matrix population models are widely applied in conservation ecology to help predict future population trends and guide conservation effort. Researchers must decide upon an appropriate level of model complexity, yet there is little theoretical work to guide such decisions. In this paper we present an analysis of a stage-structured model, and prove that the model's structure can be simplified and parameterised in such a way that the long-term growth rate, the stable-stage distribution and the generation time are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Our findings generally support their result, although our data set also included several herbaceous and woody species whose elasticity values showed an opposite pattern. Similar to Yearsley and Fletcher (2002), we observed that the elasticity of l to fecundity increased due to reduced matrix dimensionality. When matrices of different sizes are compared, it is important to be aware that some differences in elasticity values among matrices may be artifacts caused by different matrix dimensionalities.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Our findings generally support their result, although our data set also included several herbaceous and woody species whose elasticity values showed an opposite pattern. Similar to Yearsley and Fletcher (2002), we observed that the elasticity of l to fecundity increased due to reduced matrix dimensionality. When matrices of different sizes are compared, it is important to be aware that some differences in elasticity values among matrices may be artifacts caused by different matrix dimensionalities.…”
Section: Discussionsupporting
confidence: 71%
“…Although a narrow classification produces a larger matrix describing population dynamics more accurately, more data are required to produce reliable estimates compared to a wider classification (Caswell 1997). Hence, matrix dimensionality affects the reliability of estimated transition probabilities, λ, and the elasticity of λ (Vandermeer 1978, Moloney 1986, Enright et al 1995, Yearsley and Fletcher 2002).…”
mentioning
confidence: 99%
“…Moreover, other algebraic relationships than (1) could be used to collapse into . In particular, it is mathematically feasible to collapse a transition matrix into a smaller matrix while maintaining the same dominant eigenvalue and eigenvectors [10], [25], [28][30]. If such algebraic relationships were to be used rather than (1) to collapse matrices (and there is no theoretical reason for not doing it) then, by construction, would not depend on the class width.…”
Section: Methodsmentioning
confidence: 99%
“…The life cycles also contain “fertility arrows,” specifying reproduction from adult stages back to the first developmental stage. Life cycle graph construction deserves careful thought, and Caswell (2001), Yearsley and Fletcher (2002) and Cooch et al (in press) provide more treatment of this topic.…”
Section: Overview Of Demographic Conceptsmentioning
confidence: 99%